The Haunting of L.S. Lowry: Class, Mass Spectatorship and the Image at The Lowry, Salford, UK - Zoë Thompson (Societies, 2013)
In a series of momentary encounters with the surface details of The Lowry Centre, a cultural venue located in Salford, Greater Manchester, UK, this article considers the fate of the image evoked by the centre’s production and staging of cultural experience. Benjamin’s notion of ‘aura’ as inimical to transformations of art and cultural spectatorship is explored, alongside its fatal incarnation in Baudrillard’s concept of ‘simulation’. L.S. Lowry, I argue, occupies the space as a medium: both as a central figure of transmission of the centre’s narrative of inclusivity through cultural regeneration, and as one who communes with phantoms: remainders of the working-class life and culture that once occupied this locale. Through an exploration of various installations there in his name, Lowry is configured as a ‘destructive character’, who, by making possible an alternative route through its spaces, refuses to allow The Lowry Centre to insulate itself from its locale and the debt it owes to its past.